Partisipasi Masyarakat Dalam Program Corporate Social Responsibility PT. Arutmin Nort Pulau Laut Coal Terminal Kotabaru (Studi Tentang Program Koperasi Serba Usaha Madani Kotabaru) - Muhdar Muhdar; Jamaludin Jamaludin; Irwansyah Irwansyah (Universitas Lambung Mangkurat, 2014)
In addition to contributing businesses, companies should also contribute socially through the implementation of Corporate Social Responsibility (CSR). Many notions of CSR, but the essence is the company's commitment to positively impact and reduce the negative impacts of the company for the welfare of society and the environment by taking into account aspects of the triple bottom lines. PT Arutmin NPLCT is one company in Indonesia which is committed in implementing CSR. One of them is through the KSU Madani program.This study used a qualitative approach is supported with quantitative data. The strategy used in this study is to describe a program by conducting interviews, observation and document analysis.Selection of survey respondents do intentionally (purposive sampling), the number of respondents who are involved in the process of formation of KSU Madani is 21man. While the key informants is CD ComDev Dept. Officer.Results showed that the image of the KSU program Madani at the planning stage (decision-making) in the KSU Madani program has been realized with the participation of civil society in the meetings. It is clearly visible and has been implemented in this KSU Madani program, participants had a high level of presence in each meeting so that they can take decisions together by consensus. During the implementation phase KSU Madani program participants not only participate in but also contribute ideas embodied in the form of initial equity cooperatives, and participation in the management of KSU Madani program. While on stage monitoring has been realized in the form of participation of the majority of participants in a cooperative supervisory position or not all participants can conduct surveillance or monitoring directly because of limitations in terms of duties and powers that have been agreed upon.Level of community participation in the Program KSU Madani generally is high in planning and implementation, but at the stage of monitoring is low. Participation in planning and implementing high because in the process of planning the training program is conducted and decided by a meeting forum for dialogue with participants and communities involved in decision-making. While on stage due to lower monitoring not all participants can conduct surveillance program because of limited authority.Keywords: Public Participation, Corporate Social Responsibility.